Relation between Walash and Kolosh Formations and geology of their equivalent metamorphosed greywackes and arenites in Sulaimaniyah Governorate, Kurdistan Region, Northeast Iraq - Kamal H. Karim; Bashdar J. Hamza (Tikrit Journal of Pure Science, 2023)
The previous studies documented the tectonics setting, petrology, and geochemistry of the Penjween area (with Shalair Valley) before 70 years and considered it as an area of igneous rocks, and tectonically composed of three thrust sheets. According to these studies, the area includes two main igneous rock units: The Penjween Ophiolite Complex comprised of gabbro, peridotite, and granitoid intrusions at the south. The second unit is Kata Rash Volcanic rocks (Kata Rash conglomerate of the present study) which are located in the north and northeast and comprised of mafic, intermediate and felsic volcanic rocks. The present study disagrees with the previous documentation of these rocks and changed the claimed Kata Rash Volcanic Rocks and Penjween Ophiolite to metamorphosed conglomerates and coarse sandstones of the proximal facies that belong to metamorphosed sediments of Walash Formation (or Group) that was deposited in a large Paleocene Foreland Basin. The Walash Group and Kolosh Formation (as unmetamorphosed, coarse and fine sandstones or greywackes) were deposited as deep basin distal facies in the basin while Kata Rash Conglomerate belongs to coastal facies. All the above five units are deposited by turbidity currents during Paleocene-Eocene and they correlated, in the present study, stratigraphically along the basin paleodip from the present location of the Shalair valley to the south of Sulaymaniyah City. The Naopurdan Formation is recognized for the first time in the Penjween area and its facies and foraminifera are documented and correlated with Sinjar Formation. The above siliciclastic sediments were derived from volcanic source areas inside Iran and depending on the field, lab, and evaluations of the previous studies, the present study drew sedimentary stratigraphic columns and cross-sections for the Penjween and Sulaimanyiah areas and correlated their units along 100 km across the latter two areas. The correlation linked the Kolosh Formation with stratigraphic units of the Penjween area for the first-time supposing deposition during Paleocene-Eocene and sharing the same foreland basin which is aided by the first record of the occurrence of the Kolosh Formation in Chwarta by nannofossils and petrography.